FairyPlay: Recycling Trash in Hans Christian Andersen’s Fairy Tales and Children’s Play - Toft, Herdis (Aktualitet - Litteratur, kultur og medier, 2019)
Hans Christian Andersen is a cultural icon in the Danish community, and his fairy tales are canonized as treasured Danish cultural heritage. However, situated as they are today in a cross-cultural mix between folklore, booklore and medialore, they may also be analyzed as useful, treasured trash in a play culture where children recycle them in transmitted, transformed and transgressive modes. In these processes, the children perform what will be termed FairyPlay. In this article, I present Hans Christian Andersen as an intimate connoisseur of play culture, a homo ludens, a trash-sculptor and a thingfinder, like Pippi Longstocking and like children in play.